Investigation of Factors Affecting Nurses' Awareness of Child Abuse and Neglect - Ömer Faruk BAĞ; Gülçin BOZKURT (Atatürk University, 2021)
Aim: The aim of this study is to examine the factors affecting nurses' awareness about child neglect and abuse Methods: Data of the descriptive study was obtained from nurses working in Istanbul. The sample of the study consisted of 391 nurses who completed the online surveys completely during the data collection period. The research data were obtained using the Personal Information Form and the Scale for the Diagnosis of Symptoms and Risks of Child Abuse and Neglect. Results: Nurses who participated in the study; The mean age was 32.5 ± 8.4 years, 72.4% were women and 71.6% were university graduates. There was a statistically significant difference (p <0.05) in terms of total scale scores and subscale scores of Diagnosis Scale of Symptoms and Risks of Child Abuse and Neglect according to the nurses' working time (p <0.05). Being a woman, having a longer working time, having difficulty in identifying abuse and neglect, and encountering child sexual abuse increased the total score of the Scale for Diagnosing Symptoms and Risks of Child Abuse and Neglect (p <0.05). Conclusion: Women nurses, those who have longer working hours and who have encountered child sexual abuse are more aware of child neglect and abuse. Key Words: ;; neglect; abuse.